Impact of Nonlinear Anisotropic Magnetic Behavior Models on Iron Loss Modeling in Transformers - Drappier, Joël; Guyomarch, Frédéric; Cherif, Riheb; Le Menach, Yvonnick (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
This paper explores the implications of nonlinear anisotropic behavior models on the simulation of magnetic losses in a transformer made of a conventional Grain-Oriented Electrical Steel (GOES) within a finite element method (FEM) simulation environment. GO laminations are commonly used to improve the efficiency of electrical machines, but their complex behavior requires accurate modeling. Nonlinear resolutions for different anisotropy models were implemented and compared with isotropic nonlinear and linear anisotropic models. Then, the iron losses were estimated using an anisotropic model developed by Appino et al..